Approach to the diagnosis of drug hypersensitivity reactions: similarities and differences between Europe and North America. Issue 1 (13th March 2017) - Torres, M. J.; Romano, A.; Celik, G.; Demoly, P.; Khan, D. A.; Macy, E.; Park, M.; Blumenthal, K.; Aberer, W.; Castells, M.; Barbaud, A.; Mayorga, C.; et al.
Abstract: Drug hypersensitivity reactions (DHRs) affect an unknown proportion of the general population, and are an important public health problem due to their potential to cause life‐threatening anaphylaxis and rare severe cutaneous allergic reactions. DHR evaluations are frequently needed in both ambulatory and hospital settings and have a complex diagnosis that requires a detailed clinical history and other tests that may include in vitro tests and in vivo procedures such as skin tests and drug provocation tests. Although over the years both European and U.S. experts have published statements on general procedures for evaluating DHRs, a substantial discordance in their daily management exists. In this review, we highlight both the differences and the similarities between the European and U.S. perspectives. While a general consensus exists on the importance of skin tests for evaluating DHRs, concordance between Americans and Europeans exists solely regarding their use in immediate reactions and the fact that a confirmation of a presumptive diagnosis by drug provocation tests is often the only reliable way to establish a diagnosis. Finally, great heterogeneity exists in the application of in vitro tests, which require further study to be well validated.